2011
DOI: 10.1073/pnas.1006740108
|View full text |Cite
|
Sign up to set email alerts
|

Transkingdom signaling based on bacterial cyclodipeptides with auxin activity in plants

Abstract: Microorganisms and their hosts communicate with each other through an array of signals. The plant hormone auxin (indole-3-acetic acid; IAA) is central in many aspects of plant development. Cyclodipeptides and their derivative diketopiperazines (DKPs) constitute a large class of small molecules synthesized by microorganisms with diverse and noteworthy activities. Here, we present genetic, chemical, and plant-growth data showing that in Pseudomonas aeruginosa, the LasI quorum-sensing (QS) system controls the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
122
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(129 citation statements)
references
References 40 publications
(47 reference statements)
1
122
0
2
Order By: Relevance
“…It was suggested that L-cyclo(Pro-Phe) and L-cyclo(Pro-Leu) produced by A. faecalis played a probable role in spongebacterial interaction (Li et al 2008). The observation that QS-regulated bacterial production of DKPs modulates auxin signaling and plant growth promotion established an important function for DKPs mediating prokaryote/ eukaryote transkingdom signaling (Ortiz-Castro et al 2011). The roles of DKPs played in QS offered an alternative approach to activate or antagonize the QS-mediated biological activities, such as biofilm formation.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that L-cyclo(Pro-Phe) and L-cyclo(Pro-Leu) produced by A. faecalis played a probable role in spongebacterial interaction (Li et al 2008). The observation that QS-regulated bacterial production of DKPs modulates auxin signaling and plant growth promotion established an important function for DKPs mediating prokaryote/ eukaryote transkingdom signaling (Ortiz-Castro et al 2011). The roles of DKPs played in QS offered an alternative approach to activate or antagonize the QS-mediated biological activities, such as biofilm formation.…”
Section: Introductionmentioning
confidence: 99%
“…In plants, root genes induced by rhizospheric bacteria are involved in oxidative and defense responses, in plant secondary metabolism, or in signaling (140). Plants may detect bacterial cyclopeptides through auxin sensing pathways (147). In a more specialized symbiosis, a cascade of signaling processes occurs inside root cells in the presence of rhizobia or Nod factors (148).…”
Section: Similar Bacterium-host Interactions In Guts and Rootsmentioning
confidence: 99%
“…Especially cyclo-prolyl-phenylalanyl is discussed recently to act as a signalling mimic of the plant hormone auxin (Ortiz-Castro et al 2011;Venturi and Fuqua 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclo-isoleucyl-prolyl and cyclo-prolyl-valyl were not present in the NIST11 database. Identification was done by comparison with published fragmentation patterns (Bitzer 2005;Wang et al 2010;Ortiz-Castro et al 2011). Only extract 3 contained all mentioned molecules and the respective strain was therefore chosen for genome sequencing.…”
Section: Identification Of Secondary Metabolitesmentioning
confidence: 99%